SEASONAL VARIATIONS IN BLOOD METABOLIC PROFILES DURING PERI AND EARLY POSTPARTUM PERIOD IN WINTER AND SUMMER CALVED BUFFALOES - ABAYAWANSA, W D; PRABHAKAR, S; SINGH, A K; BRAR, P S (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on healthy, lactating pluriparous Murrah buffaloes (n = 29), calved duringDecember 2007 to May 2008. On the basis of season of calving the animals were divided into two group's viz.winter calving buffaloes (WCB) and summer calving buffaloes (SCB). During postpartum period, WCB had significantly(P < 0.05) higher blood concentration of total protein, urea nitrogen and non-esterified fatty acids whereas SCBhad significantly (P < 0.05) higher concentration of glucose, cholesterol and creatinine. Overall, fluctuations in themean concentration of various metabolic parameters were noticed in buffaloes of both the groups.
Keywords: Blood metabolic profile; Buffalo; Calving; Season